HBsAg protein composition and clinical outcomes in chronic hepatitis D and variations across HBeAg-negative chronic HBsAg carriers - Luisa Roade; Mar Riveiro-Barciela; Maria Pfefferkorn; Sara Sopena; Adriana Palom; Marta Bes; Ariadna Rando-Segura; Rosario Casillas; David Tabernero; Francisco Rodríguez-Frías; Thomas Berg; Rafael Esteban; et al. (JHEP Reports, 2023)
Background & Aims: HBsAg proteins are useful to identify HBV inactive carriers (ICs), but data on chronic hepatitis D (CHD) are scarce. This study aimed to describe HBsAg composition in CHD, its changes during the evolution, and the potential association with clinical outcomes. In addition, we assess the composition of HBsAg across different HBV genotypes and validate previous results on HBsAg proteins in an independent HBV cohort. Methods: Quantitative HBsAg, medium HBsAg proteins (MHBs), and large HBsAg proteins (LHBs) were measured in two cohorts. The first cohort consisted of patients with CHD. A cross-sectional study of samples from two European institutions (N = 46) was conducted. Outcomes were assessed in a retrospective–prospective study of those patients with a follow-up of >1 year (n = 36), and the longitudinal evolution of HBsAg proteins in those with samples >5 years apart (n = 12) was analysed. The second cohort consisted of patients with HBeAg-negative HBV, and a cross-sectional study was performed (N = 141). Results: Forty-one (89%) patients with CHD had detectable HDV-RNA, and the presence of HDV-RNA was associated with higher LHBs proportion (p = 0.010). Baseline MHBs (p = 0.051) and MHBs proportion (p = 0.086) tended to be higher in those developing clinical outcomes (9/36, 25%) after a median follow-up of 5.9 years. Patients in which HDV-RNA became spontaneously undetectable during follow-up (5/31, 16.1%) tended to present lower MHBs proportion (p = 0.085). In the longitudinal study, changes in LHBs proportion were observed (p = 0.041), whereas MHBs proportion remained stable (p = 0.209). Regarding HBV, ICs showed lower LHBs proportion (p = 0.027). LHBs and MHBs differed significantly according to HBV genotype, regardless of the HBV phase. Conclusions: Patients with CHD with detectable HDV-RNA presented higher LHBs proportion than those with undetectable HDV-RNA. A trend toward having higher baseline MHBs proportion was observed in patients who developed clinical outcomes or remained with detectable HDV-RNA. This study validates the different HBsAg composition in HBV ICs and reveals the HBV-genotype influence in HBsAg composition. Impact and implications: The composition of HBsAg in chronic hepatitis D differs in patients with detectable and undetectable HDV viral load and may help predict the likelihood of achieving undetectable HDV viraemia and the development of clinical events such as decompensation. The composition of the surface antigen is also useful to distinguish inactive carriers of HBV, and it varies according to HBV genotype.